Establishing and applying an adaptive framework for imported malaria: a field practice in Anhui Province, China from 2012 to 2022 - Tao Zhang; Xian Xu; Bowen Liu; Duoquan Wang; Xiangguang Ye; Jingjing Jiang; Shuqi Wang; Xiaofeng Lyu; Chen Yu; Cuicui Tian; Zijian Liu; Xuechun Lu; et al. (BMC, 2024)
Abstract Background Anhui Province is currently facing an increase in imported malaria cases as a result of globalization and international travel. In response, Anhui Province has implemented a comprehensive adaptive framework to effectively address this threat. Methods This study collected surveillance data from 2012 to 2022 in Anhui Province. Descriptive statistics were used to analyze the epidemiological characteristics of imported malaria cases. Additionally, multivariate logistic regression was employed to identify factors associated with severe malaria. Documents were reviewed to document the evolution of the adaptive framework designed to combat imported malaria. The effectiveness of the adaptive framework was evaluated based on the rates of timely medical visits, timely diagnosis, and species identification. Results During the study period, a total of 1008 imported malaria cases were reported across 77 out of 105 counties in Anhui Province, representing a coverage of 73.33%. It was found that 10.52% of imported cases went undiagnosed for more than seven days after onset. The multivariate analysis revealed several potential risk factors for severe malaria, including increasing age (OR = 1.049, 95%CI:1.015-1.083), occupation (waitperson vs. worker, OR = 2.698, 95%CI:1.054-6.906), a longer time interval between onset and the initial medical visit (OR = 1.061, 95%CI:1.011-1.114), and misdiagnosis during the first medical visit (OR = 5.167, 95%CI:2.535-10.533). Following the implementation of the adaptive framework, the rates of timely medical visits, timely diagnosis, and species identification reached 100.00%, 78.57%, and 100.00%, respectively. Conclusions Anhui Province has successfully developed and implemented an adaptive framework for addressing imported malaria, focusing on robust surveillance, prompt diagnosis, and standardized treatment. The experiences gained from this initiative can serve as a valuable reference for other non-endemic areas.